The Effectiveness of Itsbat Nikah Implementation as an Effort to Protect Wives in North Aceh Regency: Efektifitas Pelaksanaan Itsbat Nikah Sebagai Upaya Perlindungan Terhadap Istri Di Kabupaten Aceh Utara - Bukhari, Bukhari; Putri, Safira Hasriani (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Itsbat nikah carried out by the Aceh Government are regulated in Aceh Governor Regulation Number 25 of 2017 which states that the Implementation of Marriage Legalization (Itsbat Nikah) is carried out with the aim of helping people in Aceh who marry during the conflict, tsunami disaster and poor communities in obtaining marriage certificates. However, the imple mentation of itsbat nikah carried out by the Government has not been carried out according to the target. Especially in North Aceh Regency, there are still many married couples who have not yet been married. So this will greatly affect the legal protection of the wife. Therefore, researcher is interested in examining how the procedure for implementing itsbat nikah in North Aceh Regency is, what are the inhibiting factors for the in effectiveness of itsbat nikah in North Aceh Regency, and how the impact of implementing itsbat nikah as an effort to protect wives in North Aceh Regency is. The research method of this study used field research with an empirical juridical approach. The results of this study stated that the procedure for implementing an integrated itsbat nikah in North Aceh Regency started from registration at the District KUA, verifying files and then being tried by the Syar'iyah Court and after that the decision was issued. As for itsbat independent marriage, the procedure is the same as in other civil cases. Based on data on the itsbat nikah case in North Aceh Regency in 2015-2021 that the implementation of itsbat nikah in North Aceh Regency has not been effective, because it is not in accordance with the targets that have been determined at the beginning, there are still 24.82% who have not been certified for marriage. This is due to the limited budget from the Government and the Covid-19 that has occurred in Indonesia. So that the implementation of the itsbat nikah greatly impacts the legal protection of the wife, such as the wife's rights in terms of livelihood, inheritance, joint property, and so on.